Implementation and Evaluation of a School-Based Educational Program Targeting Healthy Diet and Exercise (DIEX) for Greek High School Students - Maria Angeli; Mary Hassandra; Charalampos Krommidas; Athanasios Kolovelonis; Vassilios Bouglas; Yannis Theodorakis (Sports, 2022)
The present study examined the effectiveness of a school-based health education program promoting healthy diet and exercise, named DIEX, implemented on adolescents. The program is based on the Theory of Planned Behavior (TPB) and is supported by life skills training. The recipients of the program were high school students (n = 367; 168 boys and 199 girls) from 14 schools in Greece who attended 10 1 h sessions implemented by their schoolteachers. Data were collected before and after the program implementation through online questionnaires for: a. attitude, intention, subjective norms, and PBC toward healthy eating; b. knowledge about healthy eating; c. exercise behavior and attitude toward the DIEX program; and d. satisfaction with the DIEX program (only post-program). The results showed that there were significant differences among the pre- and post-measures of students’ knowledge and behavior about healthy diet, as well as attitudes and satisfaction toward the program’s application. The results show that the DIEX program may have improved nutrition behavior variables. Conclusively, a theory-based behavioral intervention with skills training may result in positive behavioral changes for young students during health education in school settings with the assistance of new technologies.